An increased intake of thiamine diminishes the risk of metabolic syndrome in the Korean population with various comorbidities. Issue 3 (March 2022) - Nguyen, Hai Duc; Oh, Hojin; Kim, Min-Sun
Abstract: Background and aims: There is growing evidence that thiamine supplementation could reverse non-communicable diseases such as diabetes and cardiovascular diseases. However, the role of thiamine in metabolic syndrome (MetS) remains unclear. We hypothesized whether an increased intake of thiamine diminishes the risk of MetS in the Korean population with various comorbidities. This study aimed to assess the association between thiamine intake and MetS among adults with comorbidities. Methods: 57, 523 eligible participants aged over 18 years between 2009 and 2019 were recruited to obtain data on sociodemographic characteristics, medical history, current medications, lifestyle, and family history. A 24-h recall was used to determine thiamine intake. Odds ratio (OR) for MetS was calculated for log2-transformed thiamine intake values, subsequently predicting the risk of MetS based on the marginal effect. Results: The risk of MetS was significantly higher in subjects with comorbidities than in those without comorbidities. A doubling of daily thiamine intake was significantly associated with a decrease in MetS among adults with comorbidities by 7% (OR 0.93; 95%CI 0.89–0.97). Conclusions: The potential health benefits result from the intake of thiamine through an ordinary diet in the clinical management of MetS. Therefore, there is an ongoing need to look into these links between thiamine supplementation and MetS in well-characterized cohorts of participants with comorbidities. Highlights: MetS risk was significantly higher in women than in men. MetS risk was significantly higher in subjects with comorbidities than in those without. Intake of thiamine through an ordinary diet is a promising therapy in the clinical management of MetS.